2022
DOI: 10.1007/s13246-022-01113-7
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning measurements on an Elekta Unity MR-Linac

Abstract: Magnetic resonance-guided radiotherapy technology is relatively new and commissioning publications, quality assurance (QA) protocols and commercial products are limited. This work provides guidance for implementation measurements that may be performed on the Elekta Unity MR-Linac (Elekta, Stockholm, Sweden). Adaptations of vendor supplied phantoms facilitated determination of gantry angle accuracy and linac isocentre, whereas in-house developed phantoms were used for end-to-end testing and anterior coil attenu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 39 publications
0
28
0
5
Order By: Relevance
“…Powers et al . reported that the radiation isocenter was measured using a combination of multiple phantoms and analysis software [ 7 ]. All the results were within 0.5 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Powers et al . reported that the radiation isocenter was measured using a combination of multiple phantoms and analysis software [ 7 ]. All the results were within 0.5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…and Powers et al . reported TPR 20,10 values of 0.704 and 0.703, respectively [ 6 , 7 ]. The k q factor from IAEA technical reports series 398 was 0.989.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is advised to consult the vendor recommendations on calibration set up. The Unity has been reported to be calibrated under isocentric conditions to deliver: 1 cGy/MU at 10 cm depth and SSD = 133.5 cm [ 59 ] 69.6 cGy per 100 MU, which was the percentage depth dose at 10 cm and resulted in a calibration equivalent to 1 cGy/MU at at the beam quality of the measured system [ 60 ] 1 cGy/MU at 5 cm depth and SSD = 138.5 cm [ 61 ] …”
Section: Reference Dosimetrymentioning
confidence: 99%
“…It should also be noted that beam calibration for Unity systems was previously performed at a gantry angle of 90° or 270° in order to minimise the effect of varying cryostat liquid helium fill levels on attenuation at gantry 0° [, , 59 61 ]. When measuring beam output through the side of a water tank, the equivalent thickness of the water tank must be accounted for.…”
Section: Reference Dosimetrymentioning
confidence: 99%